Application of tergitol in liver decellularization and bioink preparation based on the obtained extracellular matrix - Mirosław, Paweł; Kosowska, Katarzyna; Serafin, Wiktoria; Piwowar, Radosław; Romanik-Chruścielewska, Agnieszka; Westphal, Kinga; Wszoła, Michał; Klak, Marta (Frontiers in Bioengineering and Biotechnology, 2025)
Biological materials derived from decellularized tissues are of great interest in the field of tissue engineering. Artificial organoids can be used in drug discovery or toxicological studies, potentially reducing the reliance on animal models. They also serve as valuable models for cancer and virology research. In the study, 13 slightly different detergent-enzymatic decellularization processes were performed. The end products of each process were evaluated for their DNA content, residual lipids, sulfated glycosaminoglycans (sGAG), collagen and detergent residues. To our knowledge, for the first time, Tergitol was used in liver decellularization. A method for detecting residual Tergitol content in the matrix was also developed. A significant reduction in DNA and fat content was achieved, as well as preservation of collagen. However, a marked loss of sGAGs was observed. The most promising variant involved gradient decellularization using Tergitol and ammonium hydroxide combined with pre-digestion by trypsin, which yielded the most favorable results and showed no cytotoxicity. A bioink was subsequently formulated from the decellularized matrix, which has potential applications in 3D bioprinting of artificial liver tissue.